Penanganan Ocean Freight Ekspor pada PT ICT Logistik Indonesia Cabang Surabaya - Yoga Pratama Putra Setianto; M. Ikhsan (Indonesian Maritime Researchers and Lecturers, 2025)
Handling of Export Ocean Freight is one of the services of PT ICT Logistik Surabaya Branch in shipping goods using. The objectives of this study are: 1. to describe the process of handling export ocean freight, 2. to describe efforts to resolve where customers feel that the handling of ocean freight activities is less than optimal, especially when processing their documents. This research was conducted at PT ICT Logistik Indonesia Surabaya Branch from February 2024 to May 2024. This research method uses a descriptive qualitative research method. Data collection techniques: observation, interviews, literature studies. The data collected is then subjected to data reduction, data presentation, and drawing conclusions. While the information used by researchers is operational staff and business development staff. The results of this study are Handling of Export Ocean Freight at PT ICT Logistik Indonesia Surabaya Branch, namely: 1. Handling of export ocean freight such as: a. Requesting SI from Shipper, b. Sending SI to Shipping for booking space, c. Obtaining proof of B/C or D/O, d. Drafting of B/L documents is done with the shipper until confirmation of approval, e. after that the ocean freight shipment is completed, and what are the documents needed such as: a. (Shipping Instruction) SI, b. (Delivery Order) D/O, c. (Booking Confirmation) B/C, d. (Bill of Loading) B/L, e. Invoice. 2. How are the efforts to resolve where customers feel that the handling of ocean freight activities is not optimal, especially when processing documents such as: services offered during ocean freight activities, especially document processing so that shippers get maximum service, namely: a. providing Telex release Bill Of Loading services, b. providing House B/L creation services at relatively affordable rates.